Panda Unit, a Mother-Baby Unit Nested in a Neonatal Care Service - Vitte, Lisa; Hauguel, Cyriaque; Benoit, Vincent; Genet, Marie-Camille; Letot, Jessica; Bruel, Henri; Delaunay, Florian; Le Roux, Pascal; Gerardin, Priscille; Devouche, Emmanuel; Apter, Gisèle (Frontiers in Psychiatry, 2022)
The PANDA unit is a full-time mother-baby hospitalisation unit based on an original model of care for vulnerable dyads. It is located within a neonatal unit allowing tripartite care (perinatal psychiatry, neonatology and post-natal care). It thus differs from traditional mother-baby units in its close links with the other perinatal care actors, allowing comprehensive health and mental health care in the immediate post-partum period. Patients admitted to the Panda Unit may have been referred during the antenatal period or taken into care in an emergency if the mother's clinical condition requires it, in the aftermath of childbirth. During their stay, the dyads are evaluated daily by the perinatal psychiatrist. This includes assessment of maternal clinical state, the newborn's development and the quality of mother-infant interactions. During the first six months of use, 24 dyads have benefited from PANDA care. Three women among 5 were admitted during the antenatal period and almost one-third were aged under 21. The first primary diagnosis during the antepartum was major depressive disorder, two-fold that of personality disorder or bipolar disorder alone. At the end of PANDA stay, close to 3 women among 4 were back to their home with their child, and an out-of-home placement was mandated for 4 infants. PANDA unit is a step towards continuous and comprehensive integrative care. The mother and baby do not leave the maternity ward, and management of mother, baby, and their interactions can start immediately after birth. Considering the importance of the first months of life in the establishment of fundamental links and bonding, PANDA offers an innovative opportunity for what we hope will be both therapeutic and preventive for at-risk dyads. The detection, and ultimately prevention and management of risk of abuse and neglect is another major challenge that this unit hopes to address from the very beginning.